Transport and Fate of Nitrate in the Streambed of a Low-Gradient Stream - Eric W. Peterson; Kelly M. Hayden (Hydrology, 2018)
The transport and fate of nitrate (NO3−) to in the top 15 cm of a streambed has been well-documented, but an understanding of greater depths is limited. This work examines the transport and fate of nitrate (NO3−) at depths of 30 cm, 60 cm, 90 cm, and 150 cm below the stream-streambed interface. Concentrations of nitrate as nitrogen (NO3-N) and chloride (Cl−) were measured in the waters from the streambed, the stream water, and the groundwater. Mixing models predicted values of ΔNO3-N, the difference between measured NO3-N and theoretical NO3-N. At a 30-cm depth, the mean ΔNO3-N value was −0.25 mg/L, indicating a deficit of NO3-N and the removal of NO3-N from the system. At deeper levels, the values of ΔNO3-N began to approach zero, reaching a mean value of −0.07 mg/L at 150 cm. The reduction of NO3-N does not appear to be controlled by vegetation, as it was not correlated to either temperature or visible light. Larger negative ΔNO3-N values (more removal) occur when stream NO3-N concentrations are higher and organic matter is present.